The effects of using GPS systems on spatial knowledge acquisition and the respective role of spatial design - Ahmadpoor, Negar (2019)
Navigation is one of the very first and common spatial behaviours that human-beings do within the physical environment; it is defined as a process of moving within the place with a goal of reaching a destination in a timely manner. This behaviour might seem to be a simple task since it is very common; however, it involves many multilevel cognitive processing and thus has received considerable attention from different disciplines. The recent emergence of Location-Based Services and the use of its popular form as mobile navigation systems by people in their everyday life have had a significant impact on navigation process. As people are increasingly using mobile navigation systems, research from a broad range of disciplines has examined the effectiveness of these systems, some of which have picked up worrying signs related to their use. One of these issues is concerned with spatial knowledge acquisition. The empirical studies, using different methods, have examined the effects of information provision by mobile navigation systems on people’s spatial knowledge acquisition; they have studied the extent of which, people who use mobile navigation systems, can comprehend the physical environment comparing to those who do not use such systems or use other types of assistance, such as physical maps; or how accurately they can remember the location of the physical elements such as landmarks and spatial organisation between them, as well as how well they can estimate distances and directions between places. These studies have often demonstrated that mobile navigation systems are not very effective tools in helping people to acquire spatial knowledge. Nonetheless, there is a lack of study on the relationship between the physical features of the physical environment and the extent of spatial knowledge acquisition by mobile navigation systems. Research has shown that the physical environment, which navigation takes place within, is known as a key determinant in helping people to acquire spatial knowledge and has found many spatial factors of the physical environment that are influential on people’s spatial knowledge acquisition, such as specific positions of landmark along the route, the form and length of routes, the shape and form of landmarks, the configurational complexity of the environment, the number of turns along a route, and the number of intersections linked together in a given setting. However, analysing the influence of such spatial factors on spatial knowledge acquisition of people using mobile navigation system has received little attention.